Economics and the crisis of ecology - Singh, Narindar (Delhi : Oxford : Oxford University Press, 1976)
This book reveals ecological dimensions of the developmental process.
Includes bibliographical references and index.
asm 22/01/2019
Loans
Keywords: Economics; Human ecology; Economic development; Environmental policy -- Economic aspects